2022
DOI: 10.3390/ijerph192113954
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Alcohol-Related Problems among College Students Who Report Binge Drinking Behavior: The Moderating Role of Food and Alcohol Disturbance

Abstract: Loneliness and alcohol misuse are common among college students and pose a threat to public health. To better understand the longitudinal association between these public health concerns we examined food and alcohol disturbance (FAD; i.e., restricting one’s caloric intake prior to drinking) as a moderator in the association between loneliness and alcohol-related problems. Participants were 456 college students from a mid-sized university who engaged in past 30-day binge drinking. The majority of participants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This study confirms previous studies that found excessive consumption of alcohol [ 32 ] and sexual risk-taking behaviour (such as multiple sexual partners and non-condom use) among fishers [ 55 ]. Studies have shown that loneliness can lead to increased consumption of alcohol [ 56 , 57 ]. For instance, Mohamed et al’s [ 56 ] study among adolescents in Sweden revealed that loneliness led to increased consumption of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…This study confirms previous studies that found excessive consumption of alcohol [ 32 ] and sexual risk-taking behaviour (such as multiple sexual partners and non-condom use) among fishers [ 55 ]. Studies have shown that loneliness can lead to increased consumption of alcohol [ 56 , 57 ]. For instance, Mohamed et al’s [ 56 ] study among adolescents in Sweden revealed that loneliness led to increased consumption of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is one of the first to longitudinally examine the associations between FAD-intoxication and alcohol use and related negative consequences (Herchenroeder et al, 2022). Moreover, to our knowledge, it is the first to utilize a RI-CLPM to decompose the between- and within-person components to aid in the study of the associations among these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is a risk factor for poor mental health and substance use among young people [53,54]. Research shows that, during the pandemic, loneliness was often provoked by limited social interaction, imposed isolation and restricted socialising activities, which decreased the frequency of substance use [55].…”
Section: Discussionmentioning
confidence: 99%